Hyperbranched Supramolecular Polymer of Tris(permethyl‐β‐cyclodextrin)s with Porphyrins: Characterization and Magnetic Resonance Imaging. Issue 8 (22nd April 2014) - Sun, Mo; Zhang, Hengyi; Hu, Xinyue; Liu, Bowen; Liu, Yu
Abstract A hyperbranched supramolecular polymer (HSP) is constructed based on the intermolecular inclusion complexation of bridged tris(permethyl‐β‐cyclodextrin) with MnIII‐porphyrin bearing poly(ethylene glycol) (PEG) side chains (MnIII‐TPP), and characterized by UV/vis absorption spectroscopy, isothermal titration calorimetry (ITC), NMR, dynamic light scattering (DLS), atomic force microscopy (AFM) and transmission electron microscopy (TEM), respectively. The presence of permethyl‐β‐cyclodextrin can stabilize the low‐valent MnII‐TPP. In vitro cell experiment indicates that this HSP has no remarkable cellular toxicity against NIH 3T3 cells. In vitro MR imaging experiment indicates a slightly increased T1 relaxivity for this HSP compared to that for the linear supramolecular polymer.